FACTOR AFFECTING GOOD UNIVERSITY GOVERNANCE IN FINANCIAL INFORMATION SYSTEM: EVIDENCE FROM UNIVERSITY OF INDONESIA - Fariha, Rani; DS, Ferdinand (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to determine the factors that affect the realization of Good University Governance in financial information governance at the University of Indonesia. The variables used in this study are transformational leadership, system quality, information quality, service quality, individual impact, and information system user satisfaction. The approach used in this research is quantitative research. Data obtained from 94 users of financial information systems were collected through questionnaires and analyzed using partial-least squares structural equation modeling (PLS-SEM). The results show that transformational leadership and service quality have a positive effect on Good University Governance. The quality of the system and the quality of information have a positive effect on the impact of individuals, and the quality of information and the quality of service affect the satisfaction of users of financial information systems. Good University Governance can be realized by integrating the vision and mission of the organization and its leaders, human resources, and quality infrastructure. Another important thing is the monitoring, evaluation, and adaptation of these three aspects according to the needs and current developments.